Effects of 24 weeks of single session combined strength and endurance training on body composition and fitness : examination of order effect - Küüsmaa, Maria (2013)
Küüsmaa, Maria 2013. Effects of 24 weeks of single session combined strength and endurance training on body composition and fitness: examination of order effect. Department of Biology of Physical Activity, University of Jyväskylä. Master’s Thesis in Science of Sport Coaching and Fitness Testing. 82 pp.